Réponse :
Explications étape par étape
Il faut bien voir que :
[tex]a^1=a\\a^2=a\times a=a\times a^1\\a^3=a\times a\times a=a\times a^2\\a^4=a\times a^3\\...\\a^{n+1}=a\times a^n\\[/tex]
1)
[tex]u_n=1,2^n+30\\u_{n+1}=1,2^{n+1}+30\\u_{n+1}-u_n=(1,2^{n+1}+30)-(1,2^n+30)=1,2^{n+1}-1,2^n\\u_{n+1}-u_n=1,2\times1,2^n-1,2^n=1,2^n(1,2-1)\\\\u_{n+1}-u_n=0,2\times1,2^n[/tex]
2)
[tex]0,2>0\\1,2>0\Rightarrow1,2^n>0\\[/tex]
Donc, pour tout n
[tex]u_{n+1}-u_n>0\Leftrightarrow u_{n+1}>u_n\\[/tex]
La suite est croissante sur |N